Lifestyle interventions affecting hepatic fatty acid metabolism. Issue 6 (November 2020) - Parry, Sion A.; Turner, Mark C.; Hodson, Leanne
Abstract : Purpose of review: Prevalence of metabolic-associated fatty liver disease (MAFLD) is increasing, and as pharmacological treatment does not exist, lifestyle interventions (i.e. diet and exercise) represent the cornerstone management and treatment strategy. Although the available data clearly demonstrate that changes in lifestyle influence intrahepatic triglyceride (IHTG) content, the mechanisms through which this is achieved are seldom investigated. Here, we review recent evidence demonstrating the influence of lifestyle interventions on hepatic fatty acid metabolism and IHTG content. Recent findings: Diet and exercise influence IHTG content through various, and often interrelated factors. These include alterations in whole-body and tissue-specific insulin sensitivity, which may influence the flux of fatty acid and lipogenic substrates to the liver, and changes in intrahepatic fatty acid synthesis and partitioning. Notably, there are only a few studies that have investigated intrahepatic fatty acid metabolism in vivo in humans before and after an intervention. Summary: Lifestyle interventions represent an effective means of influencing hepatic fatty acid metabolism. IHTG content is decreased without weight-loss either through exercise or by changing the macronutrient composition of the diet, although what the optimal macronutrient composition is to achieve this has yet to be defined.